Studi Kelayakan Kompetensi Profesional Guru Di Madrasah Ibtidaiyah Nurul Hikmah Sukajati Haurgeulis Tahun 2019 - Yuli Astuti; Abdur Rahim (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
Teacher competence is very important, so a teacher must have the ability to professionally improve the implementation of his duties in the field of education. It is useful for educating the nation's children. This feasibility study aims to formulate policies related to the quality of education improvement that is focused on the condition of proper madrasah ibtidaiyah (MI) teachers based on the professional competencies possessed by each teacher. This study uses a qualitative method with a cross sectional technique to analyze the data of each MI teacher based on academic qualifications according to the field of study he teaches. The findings of this study indicate that there are still many MI teachers who do not have undergraduate academic qualifications as stipulated in Law No. 14 of 2005 concerning Teachers and Lecturers. The ratio between the number of Elementary Schools (SD) and MI (both private and public) in Haurgeulis District is 5:1; or the number of SD is 41 consisting of 31 public elementary schools and 10 private elementary schools, while the number of MI is only 8, all of which are private. It can be argued that public interest and the government's response to MI are still relatively low, partly because there are still relatively few competent teachers. Keywords: Feasibility Study; Professional Competence; Madrasah Ibtidaiyah AbstrakKompetensi guru sangat penting, sehingga seorang guru harus memiliki kemampuan dalam peningkatan profesional pelaksanaan tugasnya di bidang pendidikan. Hal itu berguna untuk mencerdaskan anak bangsa. Studi kelayakan  ini bertujuan untuk merumuskan kebijakan yang terkait dengan mutu peningkatan pendidikan yang difokuskan pada kondisi guru madrasah ibtidaiyah (MI) yang layak berdasarkan kompetensi profesional yang dimiliki oleh setiap guru. Penelitian ini menggunakan metode kualitatif dengan teknik cross sectional (potong lintang) untuk menganalisis data setiap guru MI berdasarkan kualifikasi akademik sesuai dengan bidang studi yang diajarkannya. Hasil temuan penelitian ini menunjukkan bahwa masih banyak guru MI yang belum berkualifikasi akademik sarjana sebagaimana ditetapkan dalam  Undang-Undang No.14 tahun 2005 tentang Guru dan Dosen. Nisbah antara jumlah Sekolah Dasar (SD)  dengan MI (baik swasta maupun negeri) di Kecamatan Haurgeulis yaitu 5:1; atau jumlah SD adalah 41 terdiri atas 31 SD negeri dan 10 SD swasta, sedangkan jumlah MI baru 8, semuanya berstastus swasta. Dapat dikemukakan bahwa minat masyarakat dan respon pemerintah terhadap MI masih relatif rendah disebabkan antara lain karena guru yang berkompeten masih relatif  kurang.Kata Kunci: Studi Kelayakan; Kompetensi Profesional; Madrasah Ibtidaiyah